Types of activity of a judge at the preparatory stage to court hearings (Law and Safety, 2018)
It has been noted that the reform of the judicial and legal system is undergoing in Ukraine. Its main objective is to update the judicial branch of power to restore confidence in the court. Judicial activity is quite complex and multifunctional. Therefore, the personality of a judge, his level of qualification, competence and professionally important characteristics are of great importance for this activity.The author from the point of view of psychological science has analyzed the content of the basic normative and legal acts regulating judicial activity, as well as its content at the preparatory stage; has conducted a survey of judges on their main areas of activity during the preparation for court hearings. On this basis, the author has distinguished the following interrelated types of judge’s activities: organizational, managerial, psychological, communicative, epistemological, research, strategic and tactical, constructive, prognostic and fixative. These types are the basis of ensuring the effectiveness and efficiency of the trial process (criminal proceedings). The author has specified the task for each type of judge’s activity.It has been noted that the types of activity of a judge at the preparatory stage of court hearings: 1) are stipulated by such main groups of professionally important qualities as intellectual, psycho-physiological, perceptual, leadership, moral, communicative, socially oriented, specific, control and evaluation; 2) are provided by such basic types of competence as auto-psychological, psychological, communicative, general cultural, conflict, management, legal, informational and technological, strategic and tactical. It has been stressed that the above mentioned provisions will improve theoretical positions of forensic psychology, as well as will contribute to the development of competitive principles for the selection of judges.The author has indicated perspective directions of research: 1) definition of the main professionally important qualities and varieties of competence by substantiating and specifying the main tasks of the types of judge’s activity at the main and final stages; 2) development of a psychic profile of a judge; 3) research of the level of development of the components that determine the competence of a judge and the compilation of “Judge’s Map of Competence”; 4) determining the directions of preparation of candidates for judicial activity; 5) specification of the basic forms and criteria of their qualification assessment.
Keywords: judge; court hearing; preparatory stage; judicial activity; professionally important qualities; types of competencies